Automation of registry´s office in digital democracy age: the proceeding of registry officer in times of digital certification, metadata, and blockchain - Saraiva Andrade, Felipe; Bruno Façanha de Negreiros, André; Darlene Braga Araújo Monteiro, Maria (Seven Editora, 2023)
The present study analyzes, from the point of view of the implementation of technological mechanisms in extrajudicial notaries, which are the advantages or disadvantages of digital certification and "blockchain" technology in the era of digital democracy. The starting point was questioning whether the technology would pose risks to the existence of the positions of Notaries and Registrars. In addition, we sought to understand the need to implement technology as a way to reduce bureaucracy in real estate transactions and how it can be implemented. The objective of the research is to know the advantages and disadvantages of implementing the technology in land registry offices. It was concluded that technology cannot represent a disruptive potential to the current property registration system, but it can alleviate existing problems. The research was established through bibliographic methodology, with a qualitative approach and theoretical nature. DOI: https://doi.org/10.56238/tfisdwv1-011